Seismo-ionospheric anomalies and implications from recent GNSS observations in India and South-East Asia - Reddy, C.D. (My University, 2016)
The lithosphere and the atmosphere/ionosphere, continuously exchange energy through various coupling mechanisms. Earthquake creates waves of energy, e.g. direct shock acoustic waves (SAWs) and Rayleigh wave induced acoustic waves (RAWs). In the event of an earthquake occurring beneath the sea, atmospheric gravity waves (AGWs) are also generated. If the earthquake is large enough (Mw > 6), SAWs, RAWs and AGWs induce detectable ionospheric plasma perturbations. Inferring the seismological information from these seismo-ionospheric manifestations is the subject that pertains to ionospheric seismology. Both ground and satellite based advanced radio techniques are being used in monitoring ionospheric plasma perturbations. In this study, seismo-ionospheric anomalies and implications from recent GNSS observations in India and South-East Asia are discussed, mainly pertaining to the following. (1) From the ionospheric plasma response to 2015 Nepal earthquake, the estimated group velocity for Andaman and Indian shield regions are 2100 ms 1 and 3900 ms 1 respectively and validated from ground measurements. (2) Atmospheric acoustic resonance at 4.0 mHz and a train of wave packet of TEC variation resulting from the beat phenomenon observed at the site ‘umlh’ and (3) GNSS-based tsunami warning which is going to be promising tool in augmenting the existing tsunami warning systems.
Keywords: Earthquake; GEC; Ionosphere; Tsunami; GNSS